Loss of Local Astrocyte Support Disrupts Action Potential Propagation and Glutamate Release Synchrony from Unmyelinated Hippocampal Axon Terminals In Vitro - Sobieski, Courtney (J Neurosci, 2015)
Neuron–astrocyte interactions are critical for proper CNS development and function. Astrocytes secrete factors that are pivotal for synaptic development and function, neuronal metabolism, and neuronal survival. Our understanding of this relationship, however, remains incomplete due to technical hurdles that have prevented the removal of astrocytes from neuronal circuits without changing other important conditions. Here we overcame this obstacle by growing solitary rat hippocampal neurons on microcultures that were comprised of either an astrocyte bed (+astrocyte) or a collagen bed (−astrocyte) within the same culture dish. −Astrocyte autaptic evoked EPSCs, but not IPSCs, displayed an altered temporal profile, which included increased synaptic delay, increased time to peak, and severe glutamate release asynchrony, distinct from previously described quantal asynchrony. Although we observed minimal alteration of the somatically recorded action potential waveform, action potential propagation was altered. We observed a longer latency between somatic initiation and arrival at distal locations, which likely explains asynchronous EPSC peaks, and we observed broadening of the axonal spike, which likely underlies changes to evoked EPSC onset. No apparent changes in axon structure were observed, suggesting altered axonal excitability. In conclusion, we propose that local astrocyte support has an unappreciated role in maintaining glutamate release synchrony by disturbing axonal signal propagation. SIGNIFICANCE STATEMENT Certain glial cell types (oligodendrocytes, Schwann cells) facilitate the propagation of neuronal electrical signals, but a role for astrocytes has not been identified despite many other functions of astrocytes in supporting and modulating neuronal signaling. Under identical global conditions, we cultured neurons with or without local astrocyte support. Without local astrocytes, glutamate transmission was desynchronized by an alteration of the waveform and arrival time of axonal action potentials to synaptic terminals. GABA transmission was not disrupted. The disruption did not involve detectable morphological changes to axons of glutamate neurons. Our work identifies a developmental role for astrocytes in the temporal precision of excitatory signals.